2010
DOI: 10.1039/b924367d
|View full text |Cite
|
Sign up to set email alerts
|

Low coordinate lanthanide(ii) complexes supported by bulky guanidinato and amidinato ligands

Abstract: The preparation of a series of homoleptic, four-coordinate lanthanide(ii) complexes, [Ln(Priso)(2)] (Ln = Sm, Eu or Yb) incorporating the bulky guanidinate ligand Priso(-) ([(ArN)(2)CNPr(i)(2)](-), Ar = 2,6-diisopropylphenyl) is described. X-ray crystallography shows the complexes to be isostructural and to exhibit coordination geometries midway between tetrahedral and planar. Comparisons between the geometries of the complexes and those of the bulkier systems, [Ln(Giso)(2)] (Giso(-) = [(ArN)(2)CNCy(2)](-), Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 31 publications
1
47
0
2
Order By: Relevance
“…[18] This is the only example in Sm II chemistry where C-S bond formation between two CS 2 molecules is observed (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[18] This is the only example in Sm II chemistry where C-S bond formation between two CS 2 molecules is observed (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…The experimental study was reported previously by Jones et al, and no tractable product could be extracted although a reaction was observed. [18] From a computational point of view, the reactivity of COS requires more work since the C-O and C-S bonds are not polarized in the same way (actually, opposite polarization) so that two key intermediates can exist, [(Giso) 2 Sm(μ-η:SC-η:O)Sm(Giso) 2 ] or [(Giso) 2 Sm-(μ-η:OC-η:S)Sm(Giso) 2 ]. From these two key intermediates, one has to investigate all reaction pathways that yield carbonate and oxalate derivatives.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[11,12] Kürzlich wurde über einen Sm II -Komplex berichtet, der durch reduktive CS 2 -Kupplung zum Komplex [(Giso) 2 Sm(m-h 2 :h 2 -S 2 CSCS)Sm(Giso) 2 ] (Giso = [(ArN) 2 CNCy 2 ], Ar = 2,6-Diisopropylphenyl, Cy = Cyclohexyl) führte. [22] Durch reduktive Kopf-Kopf-Kupplung (C-C-Bindungsknüpfung) von CS 2 konnten bislang nur Ethylentetrathiolat (C 2 S 4 4À ) [13,14,16,17] oder C 2 S 4 4À -artige Thiooxalatkomplexe [15] hergestellt werden. Verglichen mit der C-C-s-Bindung im Oxalat-Dianion C 2 O 4 2À ist die C-C-s-Bindung in C 2 S 4 relativ schwach.…”
Section: àunclassified